2012
DOI: 10.1166/sl.2012.2585
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensing Properties of Chitosan by Using Quartz Crystal Microbalance Method

Abstract: Humidity adsorption kinetics of chitosan films was investigated by quartz crystal microbalance (QCM) technique. In this study, chitosan was synthesized from chitin by deacetylation process in 2.0% (v/v) acetic acid solution and then coated on QCM to measure humidity response. The Langmuir model was used to determine the adsorption rates and Gibbs free energy for various relative humidity between 11% and 94%. The average Gibbs free energy for adsorption was obtained as −12 93 kJ/mol. Our reproducible experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…To monitor the humidity level inside the chamber, we used the calibrated humidity and temperature sensor SHT31. The humidity variation process is similar to that reported previously (Hidayat et al, 2017). Moreover, the frequency resonance and frequency shift of the QCM sensor were measured using a laboratory-made frequency counter, as reported previously (Rianjanu et al, 2018a;Triyana et al, 2018).…”
Section: Methodsmentioning
confidence: 64%
See 1 more Smart Citation
“…To monitor the humidity level inside the chamber, we used the calibrated humidity and temperature sensor SHT31. The humidity variation process is similar to that reported previously (Hidayat et al, 2017). Moreover, the frequency resonance and frequency shift of the QCM sensor were measured using a laboratory-made frequency counter, as reported previously (Rianjanu et al, 2018a;Triyana et al, 2018).…”
Section: Methodsmentioning
confidence: 64%
“…The schematic illustration of the experimental setup used in the humidity test is shown in Fig. 2 and similar to that reported previously (Hidayat et al, 2017). Three types of QCM coated with nanofiber were placed at the top part inside the sensing chamber.…”
Section: Methodsmentioning
confidence: 97%
“…Response and recovery times were measured to be 40 and 60 s for the MES-1 sensor, respectively. This is relatively high compared to some humidity sensors [36,46,[48][49][50], but the MES-1 sensor still shows better response and recovery time compared to some other types of humidity sensors [51,52]. Moreover, in the previous studies, humidity sensor sensitivities have been reported to be 29.1 [53], 0.54 [54], 41.1 [55], 9.4 [56], and 23.1 Hz/%RH [57].…”
Section: Resultsmentioning
confidence: 97%
“…Work is done by Ayad et al, and Wang et al, were on the functionalisation of the conductive polymers PANI and PEI to aid in the performance of the chitosan-based QCM sensor respectively. The use of both PANI [111] and PEI [50] with chitosan have tremendously improved the performance of the sensor. However, the properties of the polymer used to functionalize with chitosan play a crucial role in determining the selectivity of the sensing layer.…”
Section: Polymer With Compositesmentioning
confidence: 99%
“…Ayad et al highlighted the improvement of the QCM sensor by using doped and dedoped Chitosan/PANI sensing layer in detecting amine compounds and alcohols. The sensitivity of the sensor has greatly increased from 26.23 Hz/mgL −1 for methylamine and 22.2 Hz/mgL −1 to 251.5 Hz/mgL −1 and 449 Hz/mgL −1 respectively for amines and alcohols [111]. This result is illustrating the selectivity of the sensing layer towards amine compounds as it only improved the sensitivity towards ethyl alcohol by about double the dedoped chitosan/PANI at 3.4 Hz/mgL −1 .…”
Section: Polymer With Compositesmentioning
confidence: 99%